Gastric phytobezoar: unusual association and resolution. Issue 814 (August 1993) - Wyatt, J. P.; Haddock, G.; Aitken, R. J.
Abstract : A 58 year old man underwent a laparotomy for intestinal obstruction, which proved to be due to intestinal pseudo-obstruction. Following a slow postoperative course, he was discovered to have a gastric phytobezoar. The association between bezoars and pseudo-obstruction has not been previously described, but might be expected. The gastric phytobezoar could not be fragmented mechanically, but it completely disappeared when enteral feeding was commenced. The possibility of a future role of enteral feeding in this situation is suggested.